Gestión administrativa para la cadena de suministros en empresas importadoras de maquinarias y repuestos - Intriago Vélez, Ronaldo Alexander (2023)
In the organizational world, supply chains in the last 3 decades have become a highly relevant structure for competitive companies, in which continuous investment is made in trained personnel, solid infrastructure, operational and digital technology in the case of information processing. In Ecuador, supply chains have been consolidated in efficient ways in some multinational companies due to the different investments mentioned, each one manages a planning of its resources based on forecasts and demands of its clients in the different business models, but throughout In recent years, the supply chain as a fundamental part of the organization has also been present in micro, small, medium and large companies, so they all present different types of planning............